2008
DOI: 10.1182/blood-2008-01-134122
|View full text |Cite
|
Sign up to set email alerts
|

PEBP2-β/CBF-β–dependent phosphorylation of RUNX1 and p300 by HIPK2: implications for leukemogenesis

Abstract: The heterodimeric transcription factor RUNX1/PEBP2-␤ (also known as AML1/ CBF-␤) is essential for definitive hematopoiesis. Here, we show that interaction with PEBP2-␤ leads to the phosphorylation of RUNX1, which in turn induces p300 phosphorylation. This is mediated by homeodomain interacting kinase 2 (HIPK2), targeting Ser 249 , Ser 273 , and Thr 276 in RUNX1, in a manner that is also dependent on the RUNX1 PY motif. Importantly, we observed the in vitro disruption of this phosphorylation cascade by multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 57 publications
5
55
0
Order By: Relevance
“…However, in that study, HIPK2 was found mutated in a very small percentage (2 out of 130 cases) so that it is difficult to justify a connection with p53 inactivation. HIPK2 cytoplasmic localization, similarly to what seen in the leukemogenesis model (Britos-Bray et al, 1998;Wee et al, 2008) (see above), was found related to high-mobility group A1 (HMGA1) overexpression leading to inhibition of p53-mediated apoptosis (Pierantoni et al, 2007). HMGA1 protein is frequently overexpressed in tumors and correlates strongly with cytoplasmic HIPK2 localization and low apoptotic index in wt p53-positive human breast cancer tissues (Pierantoni et al, 2007).…”
Section: Hipk2 Inactivation In Tumors and P53 Dysfunctionmentioning
confidence: 56%
See 1 more Smart Citation
“…However, in that study, HIPK2 was found mutated in a very small percentage (2 out of 130 cases) so that it is difficult to justify a connection with p53 inactivation. HIPK2 cytoplasmic localization, similarly to what seen in the leukemogenesis model (Britos-Bray et al, 1998;Wee et al, 2008) (see above), was found related to high-mobility group A1 (HMGA1) overexpression leading to inhibition of p53-mediated apoptosis (Pierantoni et al, 2007). HMGA1 protein is frequently overexpressed in tumors and correlates strongly with cytoplasmic HIPK2 localization and low apoptotic index in wt p53-positive human breast cancer tissues (Pierantoni et al, 2007).…”
Section: Hipk2 Inactivation In Tumors and P53 Dysfunctionmentioning
confidence: 56%
“…One important finding that supports the relationship between HIPK2, p53 and p300 for p53 apoptotic function comes from a leukemogenesis model in which the oncogene CBFb-SMMHC attenuates the p53 apoptotic function in response to DNA damage (that is, g-irradiation and VP-16) (Britos-Bray et al, 1998). CBFb-SMMHC prevents p300 phosphorylation by sequestering HIPK2 in the cytoplasm (Wee et al, 2008), which becomes the mechanistic explanation of the attenuation of the HIPK2/p53 apoptotic pathway in response to DNA damage.…”
Section: Role Of Hipk2 In P53 Acetylationmentioning
confidence: 99%
“…Indeed we previously showed a correlation between low HIPK2 expression and bad outcome in wild-type p53 expressing colon cancer tumors [14]. HIPK2 cytoplasmic localization may also affect p53 apoptotic function, following overexpression of oncogenes such as CBFb-SMMHC in a leukemogenesis model [22,23], high-mobility group A1 (HMGA1) [24] or b4 integrin in breast cancers [25]. HIPK2 can be downregulated by several E3 ubiquitin ligases such as WD40-repeat/SOCS box protein WSB-1, the RING family ligases Siah-1 and Siah-2 and, MDM2 oncogene [21].…”
Section: Discussionmentioning
confidence: 99%
“…1F). Both were previously shown to be phosphorylated (18)(19)(20). T173 phosphorylation has not been reported.…”
Section: Significancementioning
confidence: 99%